2021
DOI: 10.1007/s12571-021-01203-6
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of an early childhood development center–based agriculture and nutrition intervention in Malawi

Abstract: Malnutrition is a leading cause of death and disability among children in low-income countries. Nutrition-sensitive interventions show promise in increasing food access and improving diets. There are possible synergies of integrating these programs with other sectors, improving effectiveness by leveraging resources. However, economic evaluations of these multi-sectoral programs are limited. We aimed to estimate the cost efficiency, cost-effectiveness, benefit-cost ratio, and net benefit of using community-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A survey conducted 1 year post-trial showed that some benefits persisted (from improved nutrition to improved child development) whilst most other effects faded out. An economic evaluation found that the NEEP-IE programme had benefit–cost ratios from 3.6 to 24.7 [ 19 ]. Partially driven by the NEEP-IE trial findings, the Government of Malawi, through a grant from the World Bank, is in the process of scaling up components of the NEEP-IE package through the Investing in Early Years Program (IEYP) across 13 districts in the country [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A survey conducted 1 year post-trial showed that some benefits persisted (from improved nutrition to improved child development) whilst most other effects faded out. An economic evaluation found that the NEEP-IE programme had benefit–cost ratios from 3.6 to 24.7 [ 19 ]. Partially driven by the NEEP-IE trial findings, the Government of Malawi, through a grant from the World Bank, is in the process of scaling up components of the NEEP-IE package through the Investing in Early Years Program (IEYP) across 13 districts in the country [ 20 ].…”
Section: Introductionmentioning
confidence: 99%